Peculiarities of the functional state of the pituitary-gonadal system of the neuroendocrinal regulation in adolescent girl swith auto immune hepatitis - Chaykivska, E. F.; Dyadyushko, N. M. (Journal of Education, Health and Sport, 2020)
Girls and women make up 75% of patients with autoimmune hepatitis (AIH). The peak incidence of AIH occurs in childhood, when the disease is called juvenile AIH. The objective: to determine the features of the functional state of the pituitary-gonadal system of neuroendocrine regulation in adolescent girls with AIH. Material and methods. During 2010-2020, 66 girls of the main group AIH, patients with AIH, and 180 conditionally somatically and gynecologically healthy girls of the control group K at the age of 12-17 years were under observation. Comprehensive examination included history taking, assessment of sexual development, clinical and biochemical blood tests, determination of autoantibodies, markers of viral hepatitis, ultrasound examination of the abdominal cavity, liver biopsy (in main group). Peripheral serum hormone levels were determined in certain age groups (12, 13, 14, 15, 16 and 17 years): luteinizing hormone (LH), follicle-stimulating hormone (FSH), prolactin (PRL), thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), free thyroxine (fT4), estradiol (E2), progesterone (P4), free testosterone (fT). Results. Against the background of disorders of morphofunctional properties of the liver in 12-, 13-, 14- 15-, 16- and 17-year-old girls with AIH noted a significant decrease in the score of sexual development in all age groups compared to the same indicator in the relevant age control groups: 3.21 ± 0.40 vs. 4.94 ± 0.37, 3.46 ± 1.00 vs. 7.91 ± 0.58, 7.03 ± 1.44 vs. 11.08 ± 0.25, 7.80 ± 0.65 vs. 11.86, 10.65 ± 0.79 vs. 11.98 points. The average total level of LH in the Group AIHwas 3.77 ± 0.25 against 4.46 ± 0.10 mIU / ml in group K (p<0.01), FSH – 3.16 ± 0.12 against 4.01 ± 0.08 mIU / ml (p<0.01), PRL– 198.92 ± 6.96 vs. 282.93 ± 8.36 μIU / ml (p<0.01), E2– 124,15 ± 2.39 vs. 437.45 ± 9.59 pmol / ml (p<0.01), P4– 1.49 ± 0.09 vs. 2.78 ± 0.08 nmol / ml (p<0.01 ), fT– 1.96 ± 0.10 vs. 1.16 ± 0.04 nmol / l (p<0.01), TSH – 1.98 ± 0.05 vs. 2.15 ± 0.05 μIU / ml (p<0.03), fT3– 3.50 ± 0.06 vs. 5.46 ± 0.07 pmol / l (p<0.01), fT4– 12.54 ± 0.44 vs. 18.55 ± 0.20 pmol / l (p<0.01). Conclusions. In adolescent girls with AIH on the background of disorders of morphofunctional properties of the liver there is a delayed start of the hypothalamic-pituitary-gonadal system and suppression of hormone-producing function of the pituitary-gonadal link of the neuroendocrine system.